Comparison of three management schemes for Colorado potato beetle on early-season potatoes in Prince Edward Island - Stewart, J.G.; Dornan, A.P. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1990)
The economics of managing the Colorado potato beetle, Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) on potatoes (Solarium tuberosum) with different strategies was tested at four sites on Prince-Edward-Island in 1989. Three treatments were tested at each site: 1) an untreated check, 2) an application of Bacillus thuringiensis var. tenebrionis or rotenone after a threshold of 0.5 Colorado Potato Beetle Equivalents (CPBE) per stalk was reached ( 1 CPBE = 1 spring adult, 8 first- or second- instar larvae, 3 third- or fourth- instar larvae, or 1.6 summer adults), and 3) applications of insecticide according to the grower's normal spray schedule. At one site, tuber yield of plots managed with the 0.5 CPBE-per-stalk threshold was similar to that of plots where the grower maintained his normal spray schedule, but three fewer applications of insecticides were needed in the former. At the remaining sites, where the density of Colorado potato beetles did not exceed the threshold, tuber yield was similar to that of the grower's plots. This suggests that there were needless applications of insecticides by the growers.